Comparison Between Binuclear and Mononuclear Ru(II) Complexes: Synthesis, Structure, Photophysics, and Oxygen Sensing Performance - Wang, Fei; Yang, Liyuan; Xian, Xue-Quan (Frontiers in Chemistry, 2021)
Owing to their attractive potential in optoelectronic application, luminescent Ru(II) complexes with diamine ligands are harvesting more and more research efforts. These literature efforts, however, are mostly mononuclear ones, with no detailed discussion on the performance comparison between mononuclear and multinuclear Ru(II) complexes. This work synthesized three diamine ligands having two or multiple chelating sites in each ligand, as well as their Ru(II) complexes. The single crystal structure, electronic structure and photophysical parameters of these Ru(II) complexes were analyzed and compared. It was found that multinuclear Ru(II) complexes had a pure MLCT-based (metal-to-ligand-charge-transfer-based) emissive center, showing longer emission lifetime and higher emission quantum yield, which were desired for oxygen sensing. Then the oxygen sensing performance of these mononuclear and multinuclear Ru(II) complexes was systematically compared by doping them into polymer fibers via electrospinning method. Improved oxygen sensing performance was observed from binuclear Ru(II)-doped nanofibrous samples, compared to the sensing performance of mononuclear ones, including higher sensitivity, shorter response/recovery time and better photostability. The causation was attributed to the fact that the emissive state of multinuclear Ru(II) complexes was MLCT-based ones and thus more sensitive to O2 quenching than monocular Ru(II) complexes whose emissive state was a mixture of MLCT and LLCT (ligand-to-ligand-charge-transfer). In addition, a multinuclear Ru(II) complex had multiple emissive/sensing components, so that its sensing collision probability with O2 was increased, showing better photostability and shorter response/recovery time. The novelty of this work was the linear oxygen sensing curve which was rarely reported in previous work.